Aplikasi Bergerak dengan Java J2ME untuk Pelaporan Penyelidikan Epidemiologi Penyakit Demam Berdarah - Iman Satoto, Kodrat; Isnanto, Rizal; Aditya, Firdaus (Jurnal Sistem Komputer, 2012)
Nowadays, reporting system of Dengue Hemorrhagic Fever Epidemiologic investigation (PE DBD) in Health Department uses manual recording system. It takes more times for printing as well as for reading. This inefficient system will affect a longer decision making to handle the spread of dengue fever in Semarang. Therefore, a research is needed to overcome these problems, i.e. by developing mobile application embedded in cell phone and web application as administrator to facilitate the data management transmitted. There are several steps taken in this research. First, analyzing the existing system in Health Department. Second, designing system with Unified Modeling Language (UML). Third, developing an application using Java J2ME for client and Java J2EE for server as programming language and MySQL as database server. The last step is application testing.. Based on research results, it can be concluded that this application has been able to facilitate and accelerate the process of reporting the current PE dengue disease. Users consist of officers of PE as a user of mobile applications for data entry operator of PE DBD and P2P as web application server administrator. Through a web application, administrators can print data input PE of phone listed in the form of dynamic HTML.Permalink:Â http://jsiskom.undip.ac.id/index.php/jsk/article/view/27